Distributive and Procedural Justice as Predictors of Employee Trust: The Moderating Role of Transformational Leadership (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study investigates the role of organizational justice—specifically distributive and procedural justice—as predictors of employee trust within the workplace, emphasizing the moderating influence of transformational leadership. In today’s dynamic organizational landscape, fostering trust among employees has become critical to sustaining performance, engagement, and commitment. However, trust is often compromised when perceptions of fairness in outcomes and processes are inconsistent or poorly managed. The primary objective of this research is to examine how distributive justice (fairness in resource allocation) and procedural justice (fairness in deci-sion-making processes) influence employee trust, and to explore how transformational leadership moderates these relationships. The study employed a quantitative approach using survey data collected from 350 millennial employees across various service-sector organizations. Structural Equation Modeling (SEM) was utilized to test the hypothesized relationships. The findings indicate that both distributive and procedural justice significantly and positively influence employee trust. Moreover, transformational leadership strengthens these relationships, demonstrating its critical role in enhancing the effects of justice perceptions. Leaders who articulate a clear vision, inspire, and show of individualized consideration amplify the positive impacts of justice on trust. The synthesis of these findings underscores the importance of aligning fair organizational practices with effective leadership styles to build and maintain trust in contemporary work environments. These results provide actionable insights for human resource practices and leadership development programs. In conclusion, this study highlights that the path to cultivating employee trust lies not only in implementing fair practices but also in fostering transformational leadership behaviors that reinforce justice perceptions.